Analysis of pulling the goalie strategy in Finnish Junior Elite Leagues - Antila, M. (Haaga-Helia University of Applied Science, 2018)
The aim of the study is to produce data and data analysis of use of the pulling the goalie strategy in Finnish junior leagues. Selected leagues for the study are Finnish elite junior league of A-& B-juniors (U20 & U18).